Protecting Victims of Cybercrime in the Maritime Sector: Legal Challenges and the Absence of Specific Cybersecurity Laws in Indonesia - Hutahayan, Carlo Gambino; Easyca, Yesarela; Panjaitan, Junifer Dame (UNISSULA, 2025)
Indonesia's shipping sector faces substantial risks from cyberattacks in the ever-evolving digital landscape, which threaten navigation systems, ship operations, and critically impact victims, including shipping companies, crews, and passengers. This paper examines the legal challenges encountered by Indonesia's maritime industry in addressing cybercrime, with a particular focus on the lack of dedicated cybersecurity laws that explicitly protect victims. The research findings reveal that Law No. 11 of 2008 on Information and Electronic Transactions and Law No. 17 of 2008 on Shipping are inadequate in addressing the specific cyber threats and victim protection needs within the maritime sector. This study advocates for the establishment of specialized regulations incorporating clear definitions and scope, detailed obligations and responsibilities, robust victim protection measures, appropriate security standards, and effective enforcement mechanisms and sanctions. By integrating these elements, the research offers both theoretical and practical guidance for policymakers to develop a more comprehensive and adaptive regulatory framework that not only secures Indonesia's maritime infrastructure but also ensures justice and support for victims of maritime cybercrime.